Comparative study between low level laser and therapeutic ultrasound in second intention ulcers repair in mice - de Sousa, Aline Carla Teles; da Rocha, Ítalo Bruno Paiva; de Carvalho, Ana Flávia Machado; de Freitas Coelho, Nayana Pinheiro Machado; Feitosa, Maura Cristina Porto; Barros, Esmeralda Maria Lustosa; Arisawa, Emilia Angela Lo Schiavo [UNESP]; de Amorim, Maria Rosilândia Lopes (Maad Rayan Publishing Company, 2018)
Introduction: An ulcer is an injury that affects the skin and has many causes. Healing is a way of protecting the body against any infectious agent that tries to infect you through the wound. Low level laser (LLL) in the treatment of ulcers, aims at maintaining the stability of the physiological process of tissue repair and ultrasound (US) acts by increasing the elasticity of tissue and scarring. The aim of this study was to analyze the effects of LLL and US in wound healing of ulcers induced in mice. Methods: In this experimental study, a sample of 36 guinea pigs was divided into 6 groups of 6 mice, 2 groups as control (C7) and (C14), 2 treated with laser (GL7) and (GL14) and the others 2 treated with ultrasound (GU7) and (GU14). The ulcer was induced and after 7 days, 6 mice from each group were sacrificed to obtain the histological sections for analysis, and the remaining 6 mice from each group continued under treatment and in day 14, they were sacrificed to obtain histologic specimens while macroscopic image was also carried out. Results: Three aspects were analyzed, the percentage of wound regression where it was observed that there was a significant difference in the first 7 days. Regarding the inflammatory process, it was observed that in the first 7 days GL7 and GU7 improved significantly and within 14 days of the experimental period GU14 showed a significant difference when compared to C14. The number of fibroblasts present in the GL at 7 days showed a significant difference compared to the others, and at 14 days, the US group had a significant difference compared to the other groups. Conclusion: Thus, it was evident that the US had more effective results with anti-inflammatory action, better organization and increased deposition of collagen and fibroblasts. Therefore, it can be concluded that other studies are consistent with this taking into account the laser must be used during the early days of the initial healing process and the US during the end of this process.
Keywords: Healing; Laser; Ulcer; Ultrasound